TGT Learning Model to Increase the Reading Ability in MA Kanjeng Sepuh Sidayu Gresik - Tiara Widyaiswara; Ali Nuke Affandy; Nikmatus Sholikhah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This research aims to increase student’s reading ability in English through question card media. The research was conducted for the XI grades at MA Kanjeng Sepuh Sidayu Gresik. The focus was describing the TGT model's implementation to increase the English reading ability in explanation text material. This research used the Classroom Action Research (CAR) method. It was conducted in two cycles, in which each process consists of planning, acting, observing, and reflecting. This study was carried out in January-March 2020. The data were collected by holding the test, monitoring, documenting, and distributing the questionnaire. The research results that the use of the TGT model in reading ability has been able to improve student’s skills. The students enjoyed and got enthusiastic. Keywords: Increase, Reading Ability, Team Games Tournament (TGT)